Graft protection of the liver by hypothermic machine perfusion involves recovery of graft regeneration in rats. Issue 1 (January 2019) - Jia, Jun-Jun; Xie, Hai-Yang; Li, Jian-Hui; He, Yong; Jiang, Li; He, Ning; Zhou, Lin; Wang, Weilin; Zheng, Shu-Sen
Objective: This study was performed to evaluate the impact and underlying mechanisms of hypothermic machine perfusion (HMP) on half-size liver graft regeneration. Methods: Forty rats were randomly assigned to five groups: two in vitro groups (static cold storage [SCS] and HMP) and three in vivo groups (orthotopic liver transplantation, SCS, and HMP). Perfusates and plasma samples were collected for analysis of hepatic enzymes. Liver tissue was obtained for evaluation of histology, immunohistochemistry (Ki67 and proliferating cell nuclear antigen [PCNA]), and the regeneration rate. Cell cycle genes were analyzed by quantitative real-time polymerase chain reaction, and cyclin D1 and cyclin E1 were semiquantified by western blot. Results: HMP improved histopathological outcomes and decreased hepatic enzyme release. The expression of Ki67 and PCNA demonstrated a greater proliferation activity in the HMP than SCS group, and the expression of almost all cell cycle genes was elevated following HMP. Western blot results showed higher protein levels of cyclin D1 and cyclin E1 in the HMP than SCS group. Conclusions: Our findings suggest for the first time that half-size liver graft protection by HMP involves recovery of graft regeneration.